Degradable porous carboxymethyl chitin hemostatic microspheres. Issue 11 (23rd July 2020) - Zhao, Yong; Li, Jiazhen; Leng, Fan; Lv, Siyao; Huang, Wei; Sun, Weiqing; Jiang, Xulin
Abstract: Lethal hemorrhage could endanger lives. Although many hemostatic agents are commercially available with good clinical effect, it is necessary to develop novel hemostatic materials with high efficacy, biological safety, low cost, easily preparation and excellent biodegradability and biocompatibility. Here, novel biodegradable and uniform microspheres with regular spherical architecture and porous microstructure were prepared by thermosensitive carboxymethyl chitin (CMCH) with low substitution degree and low deacetylation through physical-crosslinking at high temperature without using any toxic crosslinkers. The obtained CMCH microspheres (CMCH-MS) were non-cytotoxic, low hemolytic potential and biodegradable in the presence of lysozyme. In vitro blood clotting evaluation indicated that the porous microsphere network structures and the hydrophilicity of the CMCH could promote hemostasis due to the quick blood absorption and local concentration of the coagulation factors for the CMCH-MS. The CMCH-MS showed much better hemorrhage control than negative control and traditional hemostatic chitosan, similar hemostatic performance as commercialized cross-linked starch microspheres in both rat tail and liver models. Thus, the new biodegradable porous CMCH-MS may hold great potential for hemorrhage control in medical treatment. GRAPHIC ABSTRACT: